Sustainable Jam with Apple Pomace: Gelling, Rheology, and Composition Analysis - Ândria Viegas; Maria João Alegria; Anabela Raymundo (Gels)
Fruit juice processing can generate significant waste, but efficiently repurposing some of its byproducts not only reduces environmental impact but also adds value, thereby enhancing sustainability in the food industry. This work assesses the use of hydrocolloids in jam preparation and the influence of time and temperature on gelation in the presence of apple pomace. The effects of different processing conditions were analyzed using response surface methodology. Viscosity, elastic modulus (G′), viscous modulus (G″), and firmness were measured. Results indicated that both time and temperature significantly improved rheological and textural properties. The optimal conditions (35.6 min and 84.2 °C) yielded a viscosity of 3.66 × 10⁴ ± 4.49 × 102 Pa·s and a G′ at 1 Hz of 2596 ± 128 Pa. The final product exhibited the desirable texture, was free of added sugars, had low lipid content, and retained its bioactive compounds. Applying apple pomace in the formulation allows a more efficient hydrocolloid system, promotes a circular economy, and combats food waste.